L’hégémonie et les vocabulaires de la motivation punitive : la gestion discursive des crises sociales - Melossi, Dario (Criminologie, 1992)
In this paper, the author argues that, "in a given society, a process of increasing carceration occurs in cunjonction with situations perceived as critical for the maintenance of the elites' hegemony in that society (irrespective of "crimes rates"). He revisits the rich tradition inspired by Rusche's original hypothesis, but avoids the economist and instrumentalist temptations of that work. Evidence for the linkage between social structure and punishment is to be found in what he calls "vocabularies of punitive motive". He also shows that this theoretical reconstruction dovetails well with the crucial work of Foucault and other contributions to the sociology of law.